Modernism and the Portuguese Teatro de Revista - Palinhos, Jorge (Centro de Estudos Arnaldo Araújo e Instituto de História de Arte, 2015)
Largely due to the conservatism of audiences and critics, Portuguese theatre was mostly indifferent, if not downright hostile, to the avant-garde theatre coming from elsewhere in Europe. Therefore, naturalistic theatre and historical drama were the staple of Portuguese theatres until the 1950s, with the only exception of the plays of Almada Negreiros and symbolist plays by Fernando Pessoa, Raul Brandão and António Patrício. However, modernism found its place on stage in one of the most typical Portuguese theatre forms: «Revista à Portuguesa», the Portuguese revue theatre, which welcomed the first generation of Portuguese modernist painters to work as set and costume designers. Artists like Jorge Barradas, Milly Possoz, José Barbosa, among others, took the influence of the Ballets Russes of Diaghlev, and the avant-garde visual arts, to change the appearance of the most typically Portuguese theatre genre, Revista à Portuguesa. With this paper I will try to document how modernist painters gained entry in «Revista à Portuguesa» and created an art that fused the commercial interests of theatre entrepreneurs, the tastes of the bourgeois audiences and their own artistic sensibilities.
Keywords: Scenography; Teatro de Revista; Modernism; Portuguese Theatre